The International Baccalaureate in Spain - Vera Mur, José María (Avances en Supervisión Educativa, 2009)
International Bachelors Degree, also known as Programme for Diploma of International Baccalaureate, is a tertiary education course, previous to university studies, of two years duration, with a fulfilled, thorough and demanding curriculum, aimed at students with great commitment, that is taught in three languages (English, French and Spanish), and that according to the OBI (International Baccalaureate Organization) is taught in some state schools and private schools in Spain.